Role of the F-BAR Family Member PSTPIP2 in Autoinflammatory Diseases - Xu, Jie-Jie; Li, Hai-Di; Du, Xiao-Sa; Li, Juan-Juan; Meng, Xiao-Ming; Huang, Cheng; Li, Jun (Frontiers in Immunology, 2021)
Proline-serine-threonine-phosphatase-interacting protein 2 (PSTPIP2) belongs to the Fes/CIP4 homology-Bin/Amphiphysin/Rvs (F-BAR) domain family. It exhibits lipid-binding, membrane deformation, and F-actin binding activity, suggesting broader roles at the membrane–cytoskeleton interface. PSTPIP2 is known to participate in macrophage activation, neutrophil migration, cytokine production, and osteoclast differentiation. In recent years, it has been observed to play important roles in innate immune diseases and autoinflammatory diseases (AIDs). Current research indicates that the protein tyrosine phosphatase PTP-PEST, Src homology domain-containing inositol 5'-phosphatase 1 (SHIP1), and C‐terminal Src kinase (CSK) can bind to PSTPIP2 and inhibit the development of AIDs. However, the mechanisms underlying the function of PSTPIP2 have not been fully elucidated. This article reviews the research progress and mechanisms of PSTPIP2 in AIDs. PSTPIP2 also provides a new therapeutic target for the treatment of AIDs.